Clinical and surgical aspects of Dioctophyma renale parasitism in a dog - Pereira, Juliana; Mariellen Evangelista, Camila; Wyzykowski Soares, Chaiane; Polido de Araújo, Rodrigo; Viertel Molinari, Pietra; Reinert, Bruna; Luiza Soares, Sarah; Barth Wanis Figueiredo, Katherinne; de Abreu Pereira, Juliana; Dias Pedras, Franciolle (Pubvet, 2020)
Dioctophyma renale is the largest nematode that parasites the kidney of domestic, wild, and human mammals, but is found mainly in piscivorous carnivores. It is a parasite that affects more frequently the right kidney, which can cause kidney failure and lead the animal to death. The objective of this study was to report the clinical case of a male dog with 10 years of age and weight of 8 kg of Joinville municipality and to describe the surgical procedure of the nephrectomy performed for the removal of the parasite. The diagnosis of the presence of Dioctophyma renale was an accidental finding, after being performed ultrasonography, by other suspicions, and due to the greater health problems, that the dog presented, died days after the surgery.
Keywords: dioctophimosis; kidney; nephrectomy